2014
DOI: 10.1111/jop.12193
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Candida albicans ADH1 and ADH2 mRNAs in human archival oral biopsy samples

Abstract: Candida albicans was the predominant species in the lesions diagnosed as CHC, and the presence of C. albicans in CHC lesions was associated with a high expression of C. albicans ADH1 mRNA. There was no association between the presence of Candida and malignant transformation in the cases examined; however, the number of cases was limited and further studies are needed to further elucidate the role of C. albicans ADH1 in the pathogenesis of oral squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…There are conflicting results regarding the association of leukoplakia and human papillomavirus (HPV) infection [6,8]. The role of torque teno virus (TTV) [9,10], Epstein-Barr virus (EBV) [11] and Candida albicans [8,[12][13][14][15][16] in leukoplakia development and carcinogenesis remains to be clarified, too. Additionally, it has been also demonstrated that specific bacterial infections like Helicobacter pylori [17] or the intracellular Mycoplasma salivarium [18] could also be involved in this process.…”
Section: Introductionmentioning
confidence: 99%
“…There are conflicting results regarding the association of leukoplakia and human papillomavirus (HPV) infection [6,8]. The role of torque teno virus (TTV) [9,10], Epstein-Barr virus (EBV) [11] and Candida albicans [8,[12][13][14][15][16] in leukoplakia development and carcinogenesis remains to be clarified, too. Additionally, it has been also demonstrated that specific bacterial infections like Helicobacter pylori [17] or the intracellular Mycoplasma salivarium [18] could also be involved in this process.…”
Section: Introductionmentioning
confidence: 99%
“…It may promote cancer development, progression and metastasis through itsabilitytoproducecarcinogens(e.g.nitrosamines, acetaldehyde) [8,9,10,11]. ManytechniqueshavebeenusedtodetectCandida colonies.Kumaret al [12]usedvariouslaboratory testssuchasculture,germtubetest,carbohydratefermentationtest,Papanicolaou(PAP)andCalcofluor-White(CFW)stainingascytopathologicaltechniques, inadditiontotissuesectionswerestainedbyPASand CFWstaining.Inaddition,Bakriet al [5]usedPAS stain, immunohistochemistry and RT-PCR to detect Candida albicansandCaADH1mRNAgene.…”
Section: Discussionmentioning
confidence: 99%
“…TemplateRNA(14µl)wasaddedtoeachtubecontainingreverse-transcriptionmastermix,mixedand then stored on ice. The mixture was incubated for 15 min at 42°C in the thermal cycler (Biometra, USA).Thenthemixturewasincubatedinthermal cyclerfor3minat95°Ctoinactivatereversetranscriptase.TwelveandhalfµlofTopTaqwasadded to3µlCaADH1RTPCRFprimersequence(5'-3'), (CACTCACGATGGTTCATTCG),(10Pmol),3µl CaADH1RT primer sequence (5'-3'), (AAGATG-GTGCGACATTGG) [5],(10Pmol),1.5µlcDNA, then the mixture was vortexed in a total volume of 2.5 µl. Samples were put in thermal cycler for 95°C for 5 minutes (for separation of the strands), then 35 cycles of 94°C for 30 seconds, 51°C for 30 seconds (for annealing), 72°C for 60 second (for extension), then samples were put in 72°C for 10minutesforlongextension.Fivepositivecontrol sectionsof5 µm thickness eachwerescratchedfrom thepositivecontrolslidesandunderwenttheprevioustechniqueincomparisontothemarker(100bp) and study groups and had successfully ascertained thetechnique.…”
Section: Cdna Synthesis and Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…ADH activity from the human oral mucosa or microorganisms of the oral cavity are capable of oxiding ethanol to acetaldehyde, a known carcinogen (Bakri et al 2015(Bakri et al , 2014. PCR amplifications of both genes were successful and when the PCR products for both genes were run on agarose gel, it was observed that there was a clear band for both genes, ADH1B and 18s rRNA and as there was no smearing of the bands, this would indicate that there was no DNA degradation.…”
Section: Quantitative and Qualitative Assessments Of Saliva Dna From mentioning
confidence: 99%